Streptococcus pyogenes Sortase Mutants Are Highly Susceptible to Killing by Host Factors Due to Aberrant Envelope Physiology - Raz, Assaf (PLoS One, 2015)
Cell wall anchored virulence factors are critical for infection and colonization of the host by Gram-positive bacteria. Such proteins have an N-terminal leader sequence and a C-terminal sorting signal, composed of an LPXTG motif, a hydrophobic stretch, and a few positively charged amino acids. The sorting signal halts translocation across the membrane, allowing sortase to cleave the LPXTG motif, leading to surface anchoring. Deletion of sortase prevents the anchoring of virulence factors to the wall; the effects on bacterial physiology however, have not been thoroughly characterized. Here we show that deletion of Streptococcus pyogenes sortase A leads to accumulation of sorting intermediates, particularly at the septum, altering cellular morphology and physiology, and compromising membrane integrity. Such cells are highly sensitive to cathelicidin, and are rapidly killed in blood and plasma. These phenomena are not a loss-of-function effect caused by the absence of anchored surface proteins, but specifically result from the accumulation of sorting intermediates. Reduction in the level of sorting intermediates leads to a return of the sortase mutant to normal morphology, while expression of M protein with an altered LPXTG motif in wild type cells leads to toxicity in the host environment, similar to that observed in the sortase mutant. These unanticipated effects suggest that inhibition of sortase by small-molecule inhibitors could similarly lead to the rapid elimination of pathogens from an infected host, making such inhibitors much better anti-bacterial agents than previously believed.